Hak atas Kebebasan Berekspresi dan Berpendapat di Indonesia dengan di Amerika Serikat - Muhammad Roqib; Happy Anugraha Sutrisno Putra; Anwar Noris; Hotma Parlindungan Ambarita (Faculty of Law Hang Tuah University, 2020)
The right to freedom of expression and opinion is the right to freely express beliefs and opinions through words (spoken), written, printings, pictures, and certain media. But unfortunately, this right is often misused. An old maxim once said: neminem loedit qui suo iure utitur which means “he who uses a right injures no one”. Based on the maxim, a thought has been developed that use of right or authority must be an act according to law, so it is not at once caused an unlawful action. The question of this study compares legals norm between the right to freedom of expression and opinion in Indonesia and United States of America (USA). This study aims to find out the difference between legals norm of right to freedom of expression and opinion towards law system in Indonesia and USA. The right to express and hold opinion both in Indonesia and USA has been recognized as human right under the constitution. Furthermore, the right to freedom of expression and opinion in USA is protected under Virginia Bill of Rights document (June 12, 1776), Declaration of Independence (July 4, 1776), and the Act. While in Indonesia it is guaranteed by Article 28, Article 28E paragraph (2), Article 28E paragraph (3) and Article 28F in Indonesian Constitution 1945. Any restrictions on freedom of expression and opinion in USA is prescribed by court judgement, for example the case of Schenk vs US (1919) and Whitney vs California (1919). Whereas in Indonesia, limitations on the right to freedom of expression and opinion is regulated by some statutes.